Soil structural quality in pasturelands in the city of Buritis (RO), Brazil - Zebalos, Carlos Henrique; Leite, Everton Gonçalves; Monteiro, Vanessa Greztler; Lima, Ana Paula; Fogaça, Luis Gustavo; Soares, Edimar Rodrigues; Nogueira, Adriana Ema (Revista Científica da Faculdade de Educação e Meio Ambiente, 2018)
Thisstudy aims to evaluate the soil structural quality of pasturelands in the city of Buritis (RO), Brazil. The analysis took place at Boa Esperança and Boa Sorte farms, in November 2017. Three areas at Boa Esperança were evaluated: 1 –cultivation of Panicum maximum cv. Mombaça planted for 19 years; 2 –cultivation of Panicum maximum cv. Mombaça planted for two years; and 3 –cultivation of Brachiaria brizantha cv. Xaraés planted for a year and a half. The area 4 was evaluated at Boa Sorte, having Brachiariadecumbens cultivated for two years. For structural evaluation purposes, the visual examination method was deployed and grades from 1 to 6 for Soil Structural Quality Index were attributed. The average of indexes in each area was: area 1 –4,87 (good structural quality); area 2 –3,64 (regular structural quality); area 3 –4,67 (good structural quality); and area 4 –3,36 (regular structural quality). The obtained grades for areas 2 and 4 show that land use in such areas should be treated with conservationist techniques to improve overall soil structural quality over time. The good quality shown in area 1 points out that keeping fodder plants for large periods of time does not compromise overall structural quality. In this scenario, for better production results, it is only needed to improve chemical factors by fertilizing and correcting soil acid levels. The evaluation of soil structural quality is proven to be useful to help producers enhance their methods of land use, also contributing to a sustainable livestock production.